Carbon emissions efficiency in China: Key facts from regional and industrial sector. (1st January 2019) - Wang, Yong; Duan, Fumei; Ma, Xuejiao; He, Lichun
Abstract: Improving CO2 emissions efficiency has become a crucial task faced by China to develop a low-carbon economy and choose a CO2 emissions mitigation path. Existing researches have focused on estimating national CO2 emissions efficiency, but have ignored the industrial heterogeneity in the region or explanation for inefficiency. To fill the gaps, this paper applies a metafrontier-Malmquist index analysis method combined with a three-level common frontier model to comprehensively estimate and decompose the carbon emissions efficiency and dynamic changes of China's industries and regions during 2010–2015. First, we use data envelopment analysis with directional distance function by considering three-level frontiers to calculate CO2 emissions efficiency. Results show that China's overall CO2 emissions efficiency is at the middle level with an average value of 0.511. The efficiency of CO2 emissions in the eastern region is the highest, followed by the central and western regions, and the CO2 emissions efficiency in the tertiary industries is greater than that in the primary and secondary industries. Second, we decompose CO2 emissions efficiency into technological, industrial and management efficiency, and found that management efficiency is the main reason for low CO2 emissions efficiency in developed regions and industries. Third, the Malmquist-Luenberger index is utilized to decompose CO2 emissions efficiency into 9 items, and we obtained that continuous technological progress is the leading cause driving different degrees of improvement in CO2 emissions efficiency. Graphical abstract: Highlights: Apply non-radial model to estimate CO2 emissions efficiency of China. Use industrial, technical and managerial efficiency to explain inefficiency. Build three-level metafrontier-Malmquist-Luenberger index to discuss dynamic changes. Eastern region and tertiary industry have the highest CO2 emissions efficiency. Continuous technological progress is the main reason for gaps of efficiency.